Pengembangan Aplikasi Informasi Tempat Ibadah Berbasis Android (Studi Kasus: Masjid, Gereja, Pura, Wihara, dan Kelenteng di Kota Malang) - Josua Fernando; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
At the beginning of the admission of freshman year in 2018 there are at least 22,867 freshmen who will study in Malang City. One of the obstacle experienced by freshmen is the difficulty of finding a suitable place of worship. In 2014 there were 568 mosques, 1091 musalas, 92 churches for Christians, 20 churches for Catholics, five temples, eight temples, and one temple in the city of Malang. Lack of information regarding places of worship such as location, prayer schedules, speaker schedules, and public transportation routes makes it difficult for freshmen to find locations of nearby places of worship, what public transportation to ride, or places worship accordingly. So, in this research a system was developed to provide information regarding location, worship schedule, speaker schedule, and public transportation routes at places of worship using location-based services (LBS), Google Maps API and built on the native android platform. The results obtained from the development of an Android-based application, obtained 20 functional requirements and one non-functional at the requirement engineering stage. System implementation is carried out with the MVC concept (Model-View-Controller), unit testing produces 100% valid from six test cases, validation testing produces 100% valid from 38 test cases, and compatibility testing produces 100% valid on android versions 5 and 9.